2020
DOI: 10.1007/s00418-020-01928-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered vitamin D3 metabolism in the ovary and periovarian adipose tissue of rats with letrozole-induced PCOS

Abstract: Vitamin D3 (VD3) plays an important role in the ovary and its deficiency is associated with ovarian pathologies, including polycystic ovary syndrome (PCOS). However, there is no data related to VD3 metabolism in the ovary during PCOS. Herein, we investigated differences in the expression of VD3 receptor (VDR) and key VD3 metabolic enzymes, 1α-hydroxylase (CYP27B1) and 24-hydroxylase (CYP24A1), in the ovary and periovarian adipose tissue (POAT) of control (proestrus and diestrus) and PCOS induced by letrozole r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Nevertheless, it is known that vitamin D metabolism in PCOS is disrupted and, most probably, contributes to PCOS pathogenesis [105]. Thus, it is not surprising that vitamin D has a direct effect on mitochondria; it improves biogenesis and antiapoptotic parameters and upregulates the expression of antioxidants (SOD, catalase and glutathione peroxidase), which lead to a decrease in ROS levels [106].…”
Section: Mitochondria-targeted Therapymentioning
confidence: 99%
“…Nevertheless, it is known that vitamin D metabolism in PCOS is disrupted and, most probably, contributes to PCOS pathogenesis [105]. Thus, it is not surprising that vitamin D has a direct effect on mitochondria; it improves biogenesis and antiapoptotic parameters and upregulates the expression of antioxidants (SOD, catalase and glutathione peroxidase), which lead to a decrease in ROS levels [106].…”
Section: Mitochondria-targeted Therapymentioning
confidence: 99%
“…Some observational and experimental studies provide compelling evidence linking vitamin D deficiency to many of the endocrine, metabolic, and clinical components of PCOS. Vitamin D deficiency has been associated with the most prevalent phenomena in PCOS, such as hyperandrogenism [158], insulin resistance [101], adiposity indices [159], systemic proinflammatory indices, and ovulatory dysfunction [160,161]. Moreover, vitamin D is a steroid hormone with progesterone-like activity [162].…”
Section: Vitamin D and Metabolic Syndrome: Intervention Studiesmentioning
confidence: 99%
“…The findings show that vitamin D3 metabolism is disturbed in the ovary and peri-ovarian adipose tissue of rats with induced PCOS. When compared to healthy tissues, those tissues had a low concentration of 1,25(OH)2D3, implying that PCOS leads to vitamin D3 insufficiency and that this could be a factor in treating this etiology [16]. In another in vitro investigation, Sara et al found that vitamin D3 dramatically reduced systemic vascular insulin resistance in the gracilis arterioles of a DHT-treated mouse model, as well as restored systemic insulin responsiveness in these cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…Vit. D3 metabolites are not correlated with total testosterone, and SHBG Grzesiak et al, 2020 [16] Animal study Female rats allocated into the control (n=32) and letrozole-treated (n =16) groups.…”
Section: Mesinovic Et Al 2020 [15]mentioning
confidence: 99%